Edukasi Penjaminan Perlindungan Sosial Ekonomi bagi Kaum Gen Z di Komunitas Young Helper Melalui BPJS Ketenagakerjaan - Fadhil Pradwira Ilham; Riza Rivaldiansyah Daza; Aniek Irawatie; Lilik Zulaihah (Lembaga Pengembangan Kinerja Dosen, 2024)
The BPJS Employment Program is one of the crucial aspects of providing socio-economic protection for Indonesian society, especially Generation Z (Gen Z), who are entering the workforce. This service aims to enhance understanding of the BPJS Employment Program through education conducted within the Young Helper community, a volunteer organization committed to creating positive societal changes and part of Gen Z. This service also aims to increase the participatory role of Gen Z in the BPJS Employment Program, which provides socio-economic security. The method employed in this service is educational, involving interactive material presentation with data sources from literature studies, questionnaires, interviews, and field observations. Our service includes educating about the BPJS Employment Program such as eligibility criteria, technical implementation, program types, and registration procedures. The education we provide yields outputs such as pamphlets, PowerPoint presentations, educational videos, and posters, each of which highlights crucial information about the BPJS Employment Program. Our service results indicate an improvement in understanding and participatory willingness among participants to enroll in the BPJS Employment Program.